Southern Onto-Epistemology and the Prosodic Manifestation of Emotions in Gabriela Mistral’S Article Called “Chile”; [Onto-Epistemologías del Sur y Manifestación Prosódica de la Emoción en “Chile” de Gabriela Mistral] - Cid-Uribe, M (HISIN (History of Information Systems), 2025)
Introduction: Gabriela Mistral is the author of a famous prose text named “Chile,” which was published in the journal called Repertorio Americano. This essay arouses our interest to such an extent that we can analyze the prosodic manifestation of the emotions of three women who, when reading the text aloud, evoke personal experiences and engage in an emotional dialogue with the geographical, historical, anthropological, and cultural representation of the writer’s nation. Methodology: Through an interdisciplinary approach, we aim to account for ascending circumflex curvatures in relation to certain tropes present in Mistral s non-fictional literary text. Results: Initially, it is possible to demonstrate a similarity between the prosodic manifestations of emotions in the case of older speakers’s ascending circumflex curvature for the words already selected by the researchers for the purpose of measuring the prosodic manifestation of these women’s emotions. Discussions: The connection between the text s tropes and the words selected by the researchers is evident in the case of female readers between 30-49 years old. Conclusions: Although the reader in the 20-29 age range shows prosodic manifestation of her emotions, the lower presence of ascending circumflex curvatures when she read the text aloud suggests less connection with Mistral s tropes. © 2025, HISIN (History of Information Systems). All rights reserved.